The Development of Achievement Orientation Instrument (AOI) - Fagbemi, Funmi Mowaiye - (NIU Journal of Social Sciences; Vol 4 No 1 (2018): KIU Journal of Social Sciences, Vol. 4 No. 1, March 2018, 2018)
Achievement orientation is central to academic performance and high performance in any area of endeavour.  It can make the difference between excelling, mediocrity and being an average.  As the saying goes, nothing ventured, nothing gained, Genius is ninety - nine percent perspiration. Orienting towards achievement brings its own reward in performance and excellence. The achievement orientation instrument was designed in the light of growing apprehension that students, especially at the secondary school level   are not performing as excellently as previous generations of students and  that this  is  equally influencing output and invariably quality of university graduates. The instrument measures achievement orientation.